2020
DOI: 10.1038/s41398-020-01109-5
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural correlates of insomnia severity in 1053 individuals with major depressive disorder: results from the ENIGMA MDD Working Group

Abstract: It has been difficult to find robust brain structural correlates of the overall severity of major depressive disorder (MDD). We hypothesized that specific symptoms may better reveal correlates and investigated this for the severity of insomnia, both a key symptom and a modifiable major risk factor of MDD. Cortical thickness, surface area and subcortical volumes were assessed from T1-weighted brain magnetic resonance imaging (MRI) scans of 1053 MDD patients (age range 13-79 years) from 15 cohorts within the ENI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 64 publications
1
32
0
1
Order By: Relevance
“…Our main findings suggest that the PRSs for ADHD and MDD may explain a portion of the etiology of sleep disturbance regardless of current diagnostic status. Furthermore, reduced cortical areas, which are more strongly determined by genetic influences 51 , are specifically associated with insomnia severity, not with depression severity in MDD 52 . Given these findings, sleep disturbance may play a role in the intermediation between genetic risk and the onset of these psychiatric and neurodevelopmental disorders, e.g., via reduced cortical areas.…”
Section: Discussionmentioning
confidence: 87%
“…Our main findings suggest that the PRSs for ADHD and MDD may explain a portion of the etiology of sleep disturbance regardless of current diagnostic status. Furthermore, reduced cortical areas, which are more strongly determined by genetic influences 51 , are specifically associated with insomnia severity, not with depression severity in MDD 52 . Given these findings, sleep disturbance may play a role in the intermediation between genetic risk and the onset of these psychiatric and neurodevelopmental disorders, e.g., via reduced cortical areas.…”
Section: Discussionmentioning
confidence: 87%
“…These findings suggest that cortical thickness may be more reflective of an adult onset MDD subtype and chronicity, while smaller cortical surface area may reflect an early developmental subtype of depressive disorder, induced by genetic factors or early life adversity 29 . We speculate that the observed presence of cortical thickness deficiencies in the adult but not adolescent MDD sample may be due to the older mean age of the adult than adolescent MDD sample, and may be suggestive of a more pronounced effect of aging on cortical thickness in MDD versus controls69; though longitudinal studies are needed to test this hypothesis 72 …”
Section: Surface Areamentioning
confidence: 82%
“…71 Leerssen and colleagues investigated whether insomnia severity was associated with global and regional differences in cortical thickness, cortical surface areas, and volumes of subcortical regions in a sample of 1053 individuals with MDD from 15 cohorts worldwide. 72 Only cortical surface area, and neither subcortical volumes or cortical thickness, was predictive of insomnia severity in MDD. Regionally, insomnia severity was associated with smaller right insula, left inferior frontal gyrus pars triangularis, left frontal pole, right superior parietal cortex, right medial orbitofrontal cortex, and right supramarginal gyrus surface area.…”
Section: Surface Area In Major Depressive Disordermentioning
confidence: 95%
See 1 more Smart Citation
“…The inferior frontal gyrus is comprised of the orbital inferior frontal gyrus, triangular inferior frontal gyrus and opercular inferior frontal gyrus (44). The study found significant changes in frontal lobe function during sleep deprivation (45), and certain studies have suggested that functional changes in the left inferior frontal gyrus during sleep deprivation are associated with anxiety, depression and mood swings (7,43,46,47). Given the various functions of the left inferior frontal gyrus, it is difficult to distinguish whether it is the responsible center or relay station of emotion changes according to the existing research, but it is clear that the left inferior frontal gyrus is an important hub of the emotional pathways.…”
Section: Relation Of Altered Functional Connectivity To Emotion Changesmentioning
confidence: 85%